Gender Budgeting Efforts: Latin America and Canada - Pérez Fragoso, Lucía (2018)
In Latin America, gender inequality in education, health, and employment opportunities, among other areas, is long-standing, not because of isolation, as in other regions, but due especially to poorly designed economic policies and dis- crimination based on social class, age, ethnicity, sexual preference, and religious belief.Inequality has permeated five centuries of racial, ethnic and gender-based discrim- ination in the region, in societies where people are divided into first- and second-class citizens. It has permeated a modernization process built on the back of the worst income distribution in the world (ECLAC 2010).In Canada, by contrast, even though no official policy of gender budgeting exists, gender equality is advancing and gender budgeting work is crucial for pressing for government expenditure contributing to the removal of inequalities.Latin America has made progress on gender equality in recent decades, how- ever, as is evident by improvements in the Gender Development Index (GDI) (Figure 5.1).1 In every country in the region, the GDI was higher in 2013 than in the early 1990s, reflecting several changes that include the adoption of legisla- tion on equality between women and men and evolution in the institutions of government to reflect this legislation, as well as increasing representation of women in parliament and even women in the presidency in some countries...